A case study of socioeconomic influence on the use of public transport in Kota Kinabalu urban area, Malaysia - Harifah Mohd Noor; Abd Rahim Md Nor (Penerbit UMS, 2016)
This study examined the socioeconomic influence on the use of public transportation. A survey involving 987 respondents was conducted within the Kota Kinabalu city centre area. Research data was analyzed using descriptive that generated frequencies and percentages and also Chi-square tests to assess statistical relationships between two categorical variables. The results revealed that income and vehicle ownership are critical factors affecting the use of public transport. Other variables include age, employment, employment sector, marital status and a working spouse. These variables significantly affect the usage frequency of public transport by respondents. However, there are no significant statistics defining gender use of public transport. Socioeconomic variables can be utilized as a guide for relevant authorities to formulate strategies aimed at enhancing the efficiency of public transportation shortly.